2021
DOI: 10.1186/s12943-021-01346-2
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of cancer therapies by synthetic and bio-inspired nanovectors

Abstract: Background As a complement to the clinical development of new anticancer molecules, innovations in therapeutic vectorization aim at solving issues related to tumor specificity and associated toxicities. Nanomedicine is a rapidly evolving field that offers various solutions to increase clinical efficacy and safety. Main Here are presented the recent advances for different types of nanovectors of chemical and biological nature, to identify the best s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 315 publications
(384 reference statements)
0
44
0
Order By: Relevance
“…Therefore, JCPyV VLPs can be guided by a cell surface marker binding peptide for the specific delivery and transduction of a gene of interest expressed by a tissue-specific promoter in a targeted cell type. VLPs retain the characteristics of virus-specific binding to host cells, but are allowed for genetic or chemical modification to alter the tropism or increase their binding efficiency to their nature host cells 33 , 34 . For example, the specific cellular targeting of MS2 VLPs are demonstrated through attachment of a tissue specific nucleic acid aptamers 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, JCPyV VLPs can be guided by a cell surface marker binding peptide for the specific delivery and transduction of a gene of interest expressed by a tissue-specific promoter in a targeted cell type. VLPs retain the characteristics of virus-specific binding to host cells, but are allowed for genetic or chemical modification to alter the tropism or increase their binding efficiency to their nature host cells 33 , 34 . For example, the specific cellular targeting of MS2 VLPs are demonstrated through attachment of a tissue specific nucleic acid aptamers 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Research that targeting oncogenic mRNAs by siRNA is under evaluation [ 68 ]. Gene therapy can also induce cell death by delivering transgene or cell death-triggering gene to tumor cells [ 69 ].…”
Section: Nanomaterials Used For Cancer Treatmentmentioning
confidence: 99%
“…Bio-derived vesicles have drawn interest in drug and gene delivery research due to their low immunogenicity, high cellular uptake and excellent loading capacity for various cargos. 178 Recently, Kim et al developed tumorderived exosomes for Cas9 plasmid delivery. 179 They found that tumor-derived exosomes outperformed epithelial cellderived exosomes in vivo due to their cell tropism.…”
Section: Reviewmentioning
confidence: 99%